Identification of factors required for m6 A mRNA methylation in Arabidopsis reveals a role for the conserved E3 ubiquitin ligase HAKAI - Růžička, Kamil; Zhang, Mi; Campilho, Ana; Bodi, Zsuzsanna; Kashif, Muhammad; Saleh, Mária; Eeckhout, Dominique; El-Showk, Sedeer; Li, Hongying; Zhong, Silin; De Jaeger, Geert; Mongan, Nigel P; et al. (The New phytologist, 2017)
N6-adenosine methylation (m6 A) of mRNA is an essential process in most eukaryotes, but its role and the status of factors accompanying this modification are still poorly understood. Using combined methods of genetics, proteomics and RNA biochemistry, we identified a core set of mRNA m6 A writer proteins in Arabidopsis thaliana. The components required for m6 A in Arabidopsis included MTA, MTB, FIP37, VIRILIZER and the E3 ubiquitin ligase HAKAI. Downregulation of these proteins led to reduced relative m6 A levels and shared pleiotropic phenotypes, which included aberrant vascular formation in the root, indicating that correct m6 A methylation plays a role in developmental decisions during pattern formation. The conservation of these proteins amongst eukaryotes and the demonstration of a role in writing m6 A for the E3 ubiquitin ligase HAKAI is likely to be of considerable relevance beyond the plant sciences.
Keywords: proteiny huseníčku; HAKAI; adenosin; RNA, Messenger; methyltransferasy; N6-adenosine methylation (m6A); konzervovaná sekvence; mRNA methylation; Arabidopsis; Conserved Sequence; Methylation; metylace; Arabidopsis Proteins; protoxylem; Ubiquitin-Protein Ligases; ubikvitinligasy; sekvenční seřazení; Plants, Genetically Modified; VIRILIZER; Methyltransferases; geneticky modifikované rostliny; Adenosine; messenger RNA; Sequence Alignment